Selective killing of transformed rat cells by minute virus of mice does not require infectious virus production. - Guetta, E (1990)
Fischer rat fibroblasts, naturally resistant to killing by the fibrotropic strain of minute virus of mice [(parvovirus MVM(p)], became sensitive to MVM when transformed by polyomavirus. This sensitization did not involve an increase in the percentage of cells which synthesized viral capsid antigens or in the percentage of cells which produced infectious virus. The addition of anti-MVM antiserum to the growth medium of MVM-infected cells had only a small effect on their survival rates, indicating that the majority of the killing effect of MVM occurs in a single cycle of infection. The data indicate that cell killing by MVM is independent of infectious virus production and thus support the notion that the preferential cytolytic effect is affected by viral cytotoxic gene products which accumulate to intolerable levels in transformed cells but not in normal ones. Finally, using cells transformed with polyomavirus and genomic and subgenomic clones of polyomavirus, we showed that the extent of sensitization to killing by MVM depended on the transforming agent used.